Między magią a rzeczywistością: kilka uwag o specyfice realizmu doby ponowoczesnej - Kowalczyk, Monika (Er(r)go. Teoria - Literatura - Kultura, 2007)
Locating its theoretical perspective between the literary traditions of realist and fictional representation, the article revolves around the problem of postmodern literature